Lung cancer patients’ comorbidities and attendance of German ambulatory physicians in a 5-year cross-sectional study - Bossert, Jasmin; Ludwig, Marion; Wronski, Pamela; Koetsenruijter, Jan; Krug, Katja; Villalobos Bollen, Matthias Americo; Thomas, Michael; Wensing, Michel (npj Primary care respiratory medicine, 2021)
The majority of lung cancer patients are diagnosed with an advanced stage IV, which has short survival time. Many lung cancer patients have comorbidities, which influence treatment and patients’ quality of life. The aim of the study is to describe comorbidities in incident lung cancer patients and explore their attendance of ambulatory care physicians in Germany. In the observed period, 13,111 persons were first diagnosed with lung cancer (1-year incidence of 36.4 per 100,000). The mean number of comorbidities over 4 quarters was 30.77 ± 13.18; mean Charlson Comorbidity Index was 6.66 ± 2.24. In Germany, ambulatory care physicians most attended were general practitioners (2.6 quarters with contact within 4 quarters). Lung cancer was diagnosed by a general practitioner in 38% of the 13,111 incident patients. The average number of ambulatory care physician contacts over 4 quarters was 35.82 ± 27.31. High numbers of comorbidities and contacts in ambulatory care are common in patients with lung cancer. Therefore, a cross-sectoral and interdisciplinary approach is required for effective, patient-centred care. This was a 5-year cross-sectoral study, based on the InGef research database, which covers anonymized health insurance data of 7.2 million individuals in Germany. Incident lung cancer patients in a 5-year period (2013-2017) were identified. Descriptive statistics were calculated for sociodemographic characteristics, comorbidities, and attendance of ambulatory care physicians.
Gesehen am 01.12.2021